A Summary of Selective Experimental Research on Psychosocial Interventions for Sexually Abused Children. Issue 5 (3rd July 2016) - Kim, Sunah; Noh, Dabok; Kim, Hyunlye
ABSTRACT: This study was conducted to explore current trends in psychosocial interventions for sexually abused children through a review of recent research. Our comprehensive review is limited to published (quasi) experimental studies in the English language over a period of 2000–2013. It provides a detailed analysis of the final 18 articles that met our inclusion criteria, from the 670 potentially relevant articles that were identified. Reviewers analyzed candidate articles to determine whether they met inclusion or exclusion criteria. The retrieved studies reported positive results with respect to improvements in the negative psychosocial sequelae of child sexual abuse following the use of a diverse set of treatment strategies. Of the various interventions, cognitive behavioral therapy was shown to be the most promising type of intervention for sexually abused children. In this review, we discuss some of the implications of psychosocial interventions for victims of child sexual abuse, citing both the methodological and ethical issues that should be considered.